Coral reefs of Pakistan: a comprehensive review of anthropogenic threats, climate change, and conservation status - Ishfaq Ahmad; Ishfaq Ahmad; Pu Guo; Mei-Xia Zhao; Mei-Xia Zhao; Yu Zhong; Xiao-Yun Zheng; Xiao-Yun Zheng; Shu-Qi Zhang; Shu-Qi Zhang; Jian-Wen Qiu; Jian-Wen Qiu; et al. (Frontiers in Marine Science)
The coral reefs along Pakistan’s coastline are of ecological and economic significance. However, they are increasingly threatened by anthropogenic threats and climate change. These vulnerable ecosystems are declining due to various factors such as sedimentation, climate change, overfishing, destructive fishing practices, marine pollution, and tourism development. We found that 29%, 24%, 26%, 16% and 18% of the studies exceeding, marine pollution, overfishing/destructive fishing, coastal tourism, climate change and sedimentation, respectively; thus, indicating inadequate water quality status in part of Pakistan coastal water. These influences lead to several negative impacts, such as jeopardized coral health, decline in biodiversity, and the simplification of reef structures. In response to these threats, conservation efforts are imperative. This literature review provides an in-depth analysis of anthropogenic threats, climate change and the conservation of coral reefs in Pakistan. This review provides suggestions on how the country could better conserve its coral reef ecosystem. These include (1) initiatives such as establishing marine protected areas (MPAs), (2) encouraging sustainable fishing practices and reducing pollution, (3) developing the country as an ecotourism destination and implementing climate change adaptation measures, and (4) community engagement through awareness campaigns and fostering collaboration among, governmental organizations, non-governmental organizations (NGOs) and scientists. These comprehensive conservation policies address human-caused and other challenges, safeguarding their ecological, economic, and cultural relevance for future generations.